Current status and future technical advances of ultrasonic imaging. - Wells, P.N.T (IEEE Engineering in medicine and biology magazine)
Discusses current ultrasound technology in routine clinical practice, state-of-the-art technology in advanced practice, emerging technologies, and challenges in further developing the technologies. It is concluded that ultrasound imaging is an essential component in modern medical process. It is complementary to other imaging modalities; often, it is the best or even the only applicable method.